2014
DOI: 10.1007/s10811-014-0352-0
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative protocol for rapid analysis of cell density and size distribution of pelagic and benthic Microcystis colonies by FlowCAM

Abstract: Colony formation plays an important role in the life history of Microcystis. However, analyzing the colony size distribution with a microscope is time consuming, and colony formation also hinders the direct monitoring of cell density. In this study, a quantitative protocol for rapidly analyzing the cell density and colony size distribution of pelagic and benthic Microcystis was developed. Microcystis colonies were disintegrated by alkaline hydrolysis with 0.01-0.05 mol L −1 sodium hydroxide at 85°C for 6-8 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…Other investigations have similarly shown that FlowCam‐based Microcystis spp. cell abundance estimates based on these volumetric measurements were closely correlated with those determined by microscopic analyses (Lehman et al , , ; Wang et al ). In comparison, light microscopy‐based total cell counts for Aphanizomenon were often underestimated when using FlowCam (Fig.…”
Section: Instrumentationmentioning
confidence: 60%
See 1 more Smart Citation
“…Other investigations have similarly shown that FlowCam‐based Microcystis spp. cell abundance estimates based on these volumetric measurements were closely correlated with those determined by microscopic analyses (Lehman et al , , ; Wang et al ). In comparison, light microscopy‐based total cell counts for Aphanizomenon were often underestimated when using FlowCam (Fig.…”
Section: Instrumentationmentioning
confidence: 60%
“…In comparison, its use in freshwater studies is less common (Reilly‐Mathews ; Tarrant et al ; Spaudling et al ). Most studies have focused on more easily enumerated single‐celled or relatively large marine species of diatoms and dinoflagellates; however, FlowCam has also been used to reliably quantify the abundance of smaller cells of potentially toxic colonial cyanobacteria belonging to the genus Microcystis along with other phytoplankton taxa (Lehman et al , , ; Wang et al ).…”
mentioning
confidence: 99%
“…is important for securing safe water for the public [7,[10][11][12]. Biomass, cell density, and chlorophyll-a concentrations are often measured to estimate the status of algal growth [1,[13][14][15][16][17]. Counting algal cells is also important for determining the status of eutrophication in water bodies worldwide, as cell number is often included in guidelines for algal regulation, such as the World Health Organization guideline [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The FlowCam captures images of individual colonies and estimates their equivalent spherical diameter by image analysis. Wang et al [2015] showed that counts and colony diameters of Microcystis given by Flow-Cam and microscopic image analysis diameters were nearly identical. Colonies in Lake Erie are typically >50 mm [Vanderploeg et al, 2001] and buoyant.…”
Section: Measurement Of Microcystis Colony Size Distributionmentioning
confidence: 86%
“…Wang et al . [] showed that counts and colony diameters of Microcystis given by FlowCam and microscopic image analysis diameters were nearly identical. Colonies in Lake Erie are typically >50 µm [ Vanderploeg et al ., ] and buoyant.…”
Section: Methodsmentioning
confidence: 99%